Engagement of MHC class I by the inhibitory receptor LILRB1 suppresses macrophages and is a target of cancer immunotherapy. (January 2018) - Barkal, Amira; Weiskopf, Kipp; Kao, Kevin; Gordon, Sydney; Rosental, Benyamin; Yiu, Ying; George, Benson; Markovic, Maxim; Ring, Nan; Tsai, Jonathan; McKenna, Kelly; Ho, Po; et al.
Abstract Exciting progress in the field of cancer immunotherapy has renewed the urgency of the need for basic studies of immunoregulation in both adaptive cell lineages and innate cell lineages. Here we found a central role for major histocompatibility complex (MHC) class I in controlling the phagocytic function of macrophages. Our results demonstrated that expression of the common MHC class I component β2 -microglobulin (β2M) by cancer cells directly protected them from phagocytosis. We further showed that this protection was mediated by the inhibitory receptor LILRB1, whose expression was upregulated on the surface of macrophages, including tumor-associated macrophages. Disruption of either MHC class I or LILRB1 potentiated phagocytosis of tumor cells bothin vitro andin vivo, which defines the MHC class I–LILRB1 signaling axis as an important regulator of the effector function of innate immune cells, a potential biomarker for therapeutic response to agents directed against the signal-regulatory protein CD47 and a potential target of anti-cancer immunotherapy. Host cells display 'don't eat me' signals to protect themselves from phagocytosis. Maute and colleagues identify a novel 'don't eat me' system based on recognition of MHC class I by the phagocyte-expressed inhibitory molecule LILRB1.